PEMBUATAN DAN UJI PADA PAPAN PARTIKEL BERBAHAN BAKU TANDAN KOSONG KELAPA SAWIT DENGAN KOMPOSISI BAHAN YANG BERBEDA - Sitorus, Tiurma Rotua; Sakiah, Sakiah; Sutanto, Arief Setiawan (Institut Teknologi Sawit Indonesia (ITSI), 2023)
This research was conducted to determine the quality of particle board using the raw material of empty palm oil bunches with different compositions. Oil palm is a plantation crop that has an important role in Indonesia today. This plant is a plant that produces vegetable oil and its derivative products. The processing of Empty Palm Oil Bunches (EFB) into particle board as a strategy for utilizing solid waste from palm oil processing was carried out in March - June 2020. Quality tests were carried out to determine the water content, bulk density, and composition ratio of the best OPEFB-polyurethane resin for producing high-quality particle boards. The moisture content of the OPEFB fiber was obtained at 43.34%, while the maximum density and hardness of the Hardness Rockwell Scale B (HRB) can be obtained with a ratio of OPEFB fiber to resin (50: 50) 50% OPEFB and 50% resin with a bulk density of 186.70 gr/cm3 and hardness of 60 HRB. The water content affects the resistance and weight of the contents so it needs to be dried. While the high bulk density affects the particle density thereby increasing the hardness of the material. This research was conducted at the STIPAP Medan Soil and Fertilizer Laboratory and the Medan Industrial Chemical Technology Polytechnic Lab. This research was conducted in March - June 2020. This research was a descriptive study. The parameters observed were moisture content, hardness, and bulk density. The data obtained were analyzed descriptively. Based on research conducted, the greater the mass of the board, the higher the weight of the particle board. Meanwhile, the hardness of particle board is influenced by bulk density and moisture content of particle board.